Evaluation of the Effect of Laser Acupuncture and Cupping with Ryodoraku and Visual Analog Scale on Low Back Pain. (11th October 2012) - Lin, Mu-Lien; Wu, Hung-Chien; Hsieh, Ya-Hui; Su, Chuan-Tsung; Shih, Yong-Sheng; Lin, Chii-Wann; Wu, Jih-Huah
Abstract : The purpose of this study was to evaluate the effect of laser acupuncture (LA) and soft cupping on low back pain. In this study, the subjects were randomly assigned to two groups: active group (real LA and soft cupping) and placebo group (sham laser and soft cupping). Visual analog scale (VAS) and Ryodoraku were used to evaluate the effect of treatment on low back pain in this trial. Laser, 40 mW, wavelength 808 nm, pulse rate 20 Hz, was used to irradiate Weizhong (BL40) and Ashi acupoints for 10 minutes. And the Ryodoraku values were measured 2 times, that is, before and 15 minutes after treatment. The results show that there were significant difference between the first day baseline and the fifth day treatment in VAS in the two groups. Therefore, LA combined with soft cupping or only soft cupping was effective on low back pain. However, the Ryodoraku values of Bladder Meridian of the placebo group have been decreased apparently, and didn't come back to their original values. It means that "cupping" plays the role of "leak or purge" in traditional Chinese medicine (TCM). On the other hand, the Ryodoraku values of Bladder Meridian of the active group have been turned back to almost their original values; "mend or reinforcing" effect is attributed to the laser radiation.